A comparative study of efficacy and tolerability of bepotastine besilate (1.5%) and olopatadine hydrochloride (0.1%) eye drops in allergic conjunctivitis in a tertiary care hospital of the southern part of India - Sudipto Chatterjee; Vijendra R; Soumyadeep Mahapatra; Kiran Kumar L (Asian Journal of Medical Sciences, 2024)
Background: Allergic conjunctivitis is increasing with the rise in the levels of allergens. Drug therapy is usually needed in addition to avoidance of general allergens to treat this condition. Both bepotastine besilate and olopatadine hydrochloride ophthalmic solutions are newer additions in the treatment of allergic conjunctivitis having dual properties of second-generation antihistaminics along with mast cell stabilizing activity.